Probabilistic routing algorithm based on contact duration and message redundancy in delay tolerant network. (14th August 2015) - Yu, Chen; Tu, Zhongqiu; Yao, Dezhong; Lu, Feng; Jin, Hai
Summary: The Delay Tolerant Network (DTN) is a novel Wireless Sensor Network architecture for an opportunistic network environment, in which environment end‐to‐end connection cannot be set up constantly between source and destination nodes pairs. In this paper, we have proposed a novel routing algorithm based on a hybrid of message delivery probability and message redundancy to reduce the communication overhead while keeping the high message delivery ratio. In this algorithm, the message delivery probability is calculated by the combined impact of meeting frequency and length of contact duration. Further, the maximum number of copies of the message is designated in the source node, and the forwarding task of message copies is assigned to relay nodes based on the pattern of a binary tree, so that multi‐path parallel transmission can be implemented on message forwarding. Simulated results showed that the proposed routing algorithm can achieve a higher efficiency of message delivery than the related existing routing algorithms and it can also reduce the communication overhead significantly in general DTNs. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We propose a novel routing algorithm based on a hybrid of message delivery probability and message redundancy to reduce the communication overhead while keeping the high message delivery ratio. The message delivery probability is calculated by the combined impact of meeting frequency and length of contact duration. Further, the maximum number of message copies is designated in the source node, and the forwarding task of copies is assigned to relay nodes based on the pattern of a binary tree.